Early childhood professionals knowledge on accident prevention and first aid in the school (Research, Society and Development, 2022)
This study aimed to identify knowledge and experiences of early childhood education professionals concerning first aid and accident prevention in the school environment, in private primary schools in Belo Horizonte, Minas Gerais. This study used an exploratory approach, quanti-qualitative design, that was done in two private schools. Data collection was performed through interviews with 11 early childhood professionals, using a semi-structured script and the application of a questionnaire on specific knowledge about first aid, before and after conducting an educational action with participants. The study observed insufficient knowledge by professionals on this topic, insecurity in dealing with accident situations at the school and the lack of formal training. Early childhood education professionals presented weaknesses related to knowledge of first aid and accident prevention in the school environment. It is hoped that this study can encourage a new approach on the subject, offering subsidies for new interventions.